2001
DOI: 10.1073/pnas.211329998
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bt corn pollen on monarch butterfly populations: A risk assessment

Abstract: A collaborative research effort by scientists in several states and in Canada has produced information to develop a formal risk assessment of the impact of Bt corn on monarch butterfly (Danaus plexippus) populations. Information was sought on the acute toxic effects of Bt corn pollen and the degree to which monarch larvae would be exposed to toxic amounts of Bt pollen on its host plant, the common milkweed, Asclepias syriaca, found in and around cornfields. Expression of Cry proteins, the active toxicant found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
272
0
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(283 citation statements)
references
References 23 publications
6
272
0
5
Order By: Relevance
“…The results showed that larval exposure to pollen on a population-wide basis is low, given the proportion of larvae in maize fields during pollen shed, the proportion of Bt-maize fields, and the levels of pollen within and around maize fields [65]. The proportion of monarch butterfly population exposed to Bt-pollen was estimated to be less than 0.8% [66]. Field studies showed that continuous exposure of monarch butterfly larvae to natural deposits of Bt-pollen on milkweed plants within maize fields can affect individual larvae, but long-term exposure of larvae to Bt-maize pollen throughout their development is detrimental to only a fraction of the breeding population [67].…”
Section: Effects Of Bt-crops On Butterfliesmentioning
confidence: 98%
See 2 more Smart Citations
“…The results showed that larval exposure to pollen on a population-wide basis is low, given the proportion of larvae in maize fields during pollen shed, the proportion of Bt-maize fields, and the levels of pollen within and around maize fields [65]. The proportion of monarch butterfly population exposed to Bt-pollen was estimated to be less than 0.8% [66]. Field studies showed that continuous exposure of monarch butterfly larvae to natural deposits of Bt-pollen on milkweed plants within maize fields can affect individual larvae, but long-term exposure of larvae to Bt-maize pollen throughout their development is detrimental to only a fraction of the breeding population [67].…”
Section: Effects Of Bt-crops On Butterfliesmentioning
confidence: 98%
“…They also felt that the studies most likely did not address questions like the spatial and temporal overlap of monarch larvae and Bt-pollen. Extensive follow-up studies thus determined where the monarchs occur during their breeding season [65], and what percentage of the population of monarchs is possibly affected be the Bttoxin in areas where Bt-maize is presently grown [66]. The results showed that larval exposure to pollen on a population-wide basis is low, given the proportion of larvae in maize fields during pollen shed, the proportion of Bt-maize fields, and the levels of pollen within and around maize fields [65].…”
Section: Effects Of Bt-crops On Butterfliesmentioning
confidence: 99%
See 1 more Smart Citation
“…That Monarch larvae could be harmed by Bt maize pollen was not surprising, since Cry1Ab is toxic to many Lepidoptera, but in the absence in 1999 of exposure data from the field, it was impossible at the time to determine the actual risk to the populations of Monarchs. Once the exposure studies had been carried out in exemplary fashion (Sears et al, 2001), the controversy gradually disappeared. The important point is that either the risk scenario had not been identified in the initial stages of the risk assessment, or if it had been identified, it was presumed that risk was negligible, on the assumption that conditions in the over-wintering sites in Central America are more likely to determine the size of the Monarch population.…”
Section: Box 2 the Monarch Butterfly Controversy Seen In Retrospectmentioning
confidence: 99%
“…This study led to considerable debate over the environmental impact and relevance for the potential risks from Bt maize. Follow-up studies to investigate the impact of widespread plantings Bt-maize on the Monarch butterfly essentially concluded that the impact of Bt-maize pollen from current commercial hybrids on Monarch butterfly populations is negligible Oberhauser et al, 2001;Pleasants et al, 2001;Sears et al, 2001;Stanley-Horn et al, 2001;Zangerl et al, 2001). This is based on the low expression of Bt toxin genes in pollen for most maize hybrids, lack of acute toxicity at expected field rates, limited overlap of pollen shed and larval activity, and the limited overlap in distribution of Bt-maize and milkweed.…”
Section: Will Gm Crops Have Secondary Ecological Impacts?mentioning
confidence: 99%